Experimental investigation on heat recovery from flue gas using falling film method. (1st May 2021) - Min, Chunhua; Yang, Xuguang; He, Jing; Wang, Kun; Xie, Liyao; Onwude, Daniel I.; Zhang, Wenbin; Wu, Hongwei
Highlights: A new test rig based on the falling film spray technology was set up. Four different designs such as empty tower, falling film plates were proposed. The heat and moisture recovery performance from flue gas was testedsystematically. The effects of control parameters such as water–air ratio and inlet air temperature on the heat transfer effectiveness were examined. Increasing the water–air ratio or decreasing the inlet air temperature can improve the heat transfer effectiveness for all cases. Abstract: The discharge of the flue gas is rich in water vapor and its latent heat, which leads to the main heat and moisture loss for the natural gas. In this article, based on the falling film spray technology, a new test rig was set up to test the heat and moisture recovery performance from flue gas. The effects of water–air ratio and inlet air temperature on the heat transfer effectiveness were examined in a systematic manner. Four case studies, i.e. empty tower, conical baffles staggered arranged in the tower, falling film plates and baffle plates fixed on the falling film plate were designed for the current system. Experimental results showed that: (i) increasing the water–air ratio or decreasing the inlet air temperature can improve the heat transfer effectiveness; (ii) the case with conical baffles shows the highest heat transfer effectiveness. In comparison with the falling film plates, the arranged baffle plates on the falling film plate can further improve the heat transfer effectiveness; (iii) for the cases with falling plates, the heat transfer effectiveness increases with the increase of the number of the falling film plates. The maximum heat transfer effectiveness is obtained at 5 falling film plates; (iv) for the case with conical baffles, increasing the floor of the conical baffles can improve the heat transfer effectiveness. In the range of the present work, the larger central angle of the spiracle is beneficial to increase the heat transfer effectiveness. For the optimal case in the range of the present work, the heat transfer effectiveness is 41.0% higher than that for the empty tower.